W sprawie opieszałości państwa w udzielaniu rekompensaty materialnej sportowcom wycofanym z udziału w XXIII Letnich Igrzyskach Olimpijskich – medalistom zawodów „Przyjaźń 84” - Kijowski, Maciej (My University, 2015)
By the resolution of the Board of the Polish Olympic Committee of 17 May 1984, representation of Poland was withdrawn from participation in the XXIII Summer Olympic Games organized in that year in Los Angeles. The resolution was taken already in two days’ time after the Politburo of the Central Committee of the Polish United Worker’s Party had taken a decision inspiring the step of the Board of the POC, which at the same time announced providing the injured sportsmen with “moral and material satisfaction”. The paper concerns the multiyear battle to have that obligation fulfilled by the former vicechampion of the world and Europe in free-style wrestling, Jan Falandys, representing a group of sportsmen who won medals during the competition “Friendship 84”, hastily organized for communist countries, instead during the Olympic Games. Finally, by the statute of 12 January 2007 those people were granted benefits equal to benefits paid to Olympic medal winners. The Author of the paper brands the negligence of the State agencies, coming from his conviction of continuity of the Polish statehood and the unchanging relevance of decisions taken in the interest of Polish citizens, irrespective of the systemic transformation in their state.
ON THE STATE’S TARDINESS IN GRANTING MATERIAL COMPENSATION FOR SPORTSMEN WITHDRAWN FROM PARTICIPATION IN XXIII SUMMER OLYMPIC GAMES – MEDAL WINNERS OF COMPETITION “FRIENDSHIP 84”